2017
DOI: 10.18573/j.2017.10187
|View full text |Cite
|
Sign up to set email alerts
|

From Realism to Representativeness: Changing Terminology to Investigate Effectiveness in Self-Defence

Abstract: Physical assaults are an inherent problem of modern society. One strategy available to try to prevent violence is to strengthen one's personal capacities to defend oneself. This is the scope of various self-defence programs and systems within the civil domain. While training in self-defence facilitates the use of self-protective strategies in real life situations, it is important to ascertain whether individuals learn the skills taught in self-defence classes and whether they are able to perform the skills whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Denson et al (2012), for instance, showed that students who practiced self-control for two weeks by using their non-dominant hand for everyday tasks showed reduced anger, when subsequently provoked by a fictitious fellow student. Likewise, in line with the argument of training under operational constraints in order to foster skill transfer (Driskell, Salas, Johnston, & Wollert, 2008;Staller et al, 2017;Wollert, Driskell, & Quali, 2011), training under ego depleted conditions may provide the individual with the experience to cope with this internal state while displaying optimal behavior. Second, strategies aimed at reducing post-depletion aggression such as mindfulness practices (Yusainy & Lawrence, 2015) could be learned by police officers in order to reduce behavioral aggression following a depleting task.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Denson et al (2012), for instance, showed that students who practiced self-control for two weeks by using their non-dominant hand for everyday tasks showed reduced anger, when subsequently provoked by a fictitious fellow student. Likewise, in line with the argument of training under operational constraints in order to foster skill transfer (Driskell, Salas, Johnston, & Wollert, 2008;Staller et al, 2017;Wollert, Driskell, & Quali, 2011), training under ego depleted conditions may provide the individual with the experience to cope with this internal state while displaying optimal behavior. Second, strategies aimed at reducing post-depletion aggression such as mindfulness practices (Yusainy & Lawrence, 2015) could be learned by police officers in order to reduce behavioral aggression following a depleting task.…”
Section: Discussionmentioning
confidence: 81%
“…In simple terms, human behavior can be approached between the poles of stimulus control, our sub-conscious reactions to external and internal influences, and cognitive control, our capability of consciously determining thoughts, feelings, and actions (Baumeister, 2002;Burgess & Simons, 2005;Diamond, 2013;Espy, 2004;Miller & Cohen, 2001;Washburn, 2016). Cognitive control, or executive functioning (Diamond, 2013;Washburn, 2016), in police use of force situations includes (i) attentional control towards consciously and sub-consciously perceived threats (in conjunction with mechanisms associated with stimulus control; Corbetta & Shulman, 2002;Dinsmoor, 1985); (ii) working memory to interpret perceived threats; (iii) cognitive flexibility make decisions and take appropriate action; as well as (iv) inhibitory control and self-control (Chan, Shum, Toulopoulo, & Chen, 2008;Diamond, 2013;Staller, Zaiser, & Körner, 2017). This ability to inhibit, override, or to otherwise circumvent responses that are motivated by short-term rewards at the expense of long-term benefits is commonly referred to as self-control (Casey, 2015;Fujita, 2011;Hofmann, Friese, & Strack, 2009;Mischel et al, 1989;Reynolds & McCrea, 2016;Vohs & Heatherton, 2000).…”
mentioning
confidence: 99%
“…Denson et al (2012), for instance, showed that students who practiced self-control for 2 weeks by using their non-dominant hand for everyday tasks showed reduced anger when subsequently provoked by a fictitious fellow student. Likewise, in line with the argument of training under operational constraints in order to foster skill transfer (Driskell et al 2008;Staller et al 2017;Wollert et al 2011), training under ego-depleted conditions may provide the individual with the experience to cope with this internal state while displaying optimal behavior. Second, strategies aimed at reducing postdepletion aggression like mindfulness practices (Yusainy and Lawrence 2015) could be learned by police officers in order to reduce behavioral aggression following a depleting task.…”
Section: Practical Implicationsmentioning
confidence: 81%
“…In order to ensure health and safety for participants and the role player, recommendations for balancing representative testing environments with the psycho-physiological protection of involved individuals were followed (Staller et al 2017;Wollert et al 2011). Therefore, role players wore a RedMan Instructor Suit, which allows for receiving full impact blows.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…The value of physical fitness of police officers depends on the degree to which it can be applied in realistic situations (Anderson, Plecas, & Segger, 2001). To examine physical fitness in a relevant and valid manner, the testing environment must be representative for the work field (criterion environment; Staller, Zaiser, & Körner, 2017), and therefore contain relevant practical skills, constraints, and competencies needed on duty. This means that a valid test for police officers should entail how strength, endurance, and mobility are characterized during police work, and discriminate between officers who are strong, fit and able enough for police work, and those who are not.…”
Section: Introductionmentioning
confidence: 99%